Wieczór na Missisipi, czyli przyjaźń jako wstrząs - Sławek, Tadeusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2010)
<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-GB; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: PL; mso-bidi-language: AR-SA;" lang="EN-GB">The present text is an interpretation of two dialogues taken from Herman Melville’s novel The Confidence-Man. His Masquerade. One of the main topics prevailing in the conversations of the main characters from the novel traveling on the Mississippi River onboard of the steamboat “Fidéle” is friendship. Friendship, placed within the context of such notions as confidence, identity, feeling of alienation and authority, can be defined as a pre-social relation taking shape not between members of a community, but on a person-to-person plane. Another important reference point is the term “utility”, important in the capitalist “world-system” (the term coined by I. Wallerstein), which requires us to consider friendship within the framework of economic and legal circumstances and the categories of gain and loss. A juxtaposition of friendship with nature makes it finally possible to show that the former notion originates in the latter one, but exceeds it. Scientific tools used for a description of the order of nature are not precise enough to define or determine friendship between people.